Metallurgy Advances in Materials and Processes - Pardhi, Yogiraj (IntechOpen, 2012)
In recent decades scientists and engineers around the globe have been responding to the requirement of high performance materials through innovative material research and engineering. The ever increasing demand on quality and reliability has resulted in some dazzling technological achievements in the area of advanced materials and manufacturing. The purpose of this book is to bring together significant findings of leading experts, in developing and improving the technology that supports advanced materials and process development. From gold nano-structures to advanced superalloys, this book covers investigations involving modern computer based approaches as well as traditional experimental techniques. Selected articles include research findings on advances made in materials that are used not only in complex structures such as aeroplanes but also in clinical treatments. It is envisaged that it will promote knowledge transfer across the materials society including university students, engineers and scientists to built further understanding of the subject.